2007
DOI: 10.1016/j.gca.2007.09.024
|View full text |Cite
|
Sign up to set email alerts
|

Rapid biotic molecular transformation of fulvic acids in a karst aquifer

Abstract: The study of molecular transformation processes of dissolved organic carbon (DOC) in the environment significantly contributes to a better understanding of the global biogeochemical organic matter cycle. In an oxic karst groundwater system, in which the most powerful abiotic DOC degradative reactions, photodegradation and metal-mediated redox chemistry, are at best marginal contributors, a near complete turnover of fulvic acids (FAs) has been observed within decades ($60 years). Depletion of oxygen for a very … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
50
1
1

Year Published

2007
2007
2010
2010

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 67 publications
(59 citation statements)
references
References 37 publications
(47 reference statements)
7
50
1
1
Order By: Relevance
“…Besides, the highly degraded DOM in the Ave River (see also Section 3.3.5) had by far the lowest (m/z) wa and a DBE wa value closely similar to sediment pore water DOM. Furthermore, recent studies with FT-ICR-MS reported a shift to lower m/z in stream DOM and fulvic acids (Einsiedl et al, 2007), which were both exposed to microbial activity.…”
Section: Dissolved Organic Matter Characterization Via Molecular Massmentioning
confidence: 97%
See 1 more Smart Citation
“…Besides, the highly degraded DOM in the Ave River (see also Section 3.3.5) had by far the lowest (m/z) wa and a DBE wa value closely similar to sediment pore water DOM. Furthermore, recent studies with FT-ICR-MS reported a shift to lower m/z in stream DOM and fulvic acids (Einsiedl et al, 2007), which were both exposed to microbial activity.…”
Section: Dissolved Organic Matter Characterization Via Molecular Massmentioning
confidence: 97%
“…In recent years, the application of Fourier transform ion cyclotron resonance mass spectrometry (FT-ICR-MS) has been applied to the molecular characterization of DOM from different natural environments, e.g., from the marine water column (Koch et al, 2005;Hertkorn et al, 2006;Sleighter and Hatcher, 2008), rivers (Kim et al, 2003), mangrove estuaries (Koch et al, 2005;Tremblay et al, 2007), groundwater (Einsiedl et al, 2007) and soils (Kujawinski et al, 2002a;Kramer et al, 2004;Hockaday et al, 2006). FT-ICR-MS is capable of resolving complex molecular mixtures and provides information about the exact elemental composition of individual compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Heterotrophic microorganisms that thrive in fully oxygenated subsurface pools thus probably depend on other sources of OM to meet their carbon demand, e.g. compounds with no C–C bonds (methylotrophy), or recalcitrant humic substances from terrestrial sources (Einsiedl et al. , 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, natural organic matter defines the bioavailability and cycling of organic and inorganic nutrients and pollutants,3–5 making the molecular level understanding of such supermixtures essential. The proper characterization of such systems on a molecular level is feasible only if minimally invasive sampling techniques6, 7 and several high‐end analytical techniques are combined, since generally applied methods, such as elemental composition analysis, UV‐Vis and IR spectroscopy, describe them only with averaged characteristics 8, 9…”
mentioning
confidence: 99%